2015
DOI: 10.1007/s10973-015-5072-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of linear/branched polyethylene reactor blends synthesized by metallocene/late transitional metal hybrid catalysts

Abstract: Nickel diimine late transition metal (LTM) and Cp 2 TiCl 2 metallocene catalysts were supported on the TIBA-modified MgCl 2 ÁnEtOH adduct, separately and concurrently, at different ratios, to yield hybrid catalysts, where the catalytic precursors were activated in the ethylene polymerization with TEA as the cocatalyst. Polymerization activities revealed that supported LTM catalysts show very high levels of activity, in an adverse trend with polymerization temperature ranging from 30 to 70°C, in opposition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…AS in the polymerization reactor stopped the degradation by neutralizing the metal in the catalyst, because of its acid scavenging nature which resulted in a higher activity of the AS compared to AO‐1 and AO‐2. However, in the hybrid of catalysts due to the complex interaction between the catalysts, the MgCl 2 support and antioxidant showed different behaviors …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…AS in the polymerization reactor stopped the degradation by neutralizing the metal in the catalyst, because of its acid scavenging nature which resulted in a higher activity of the AS compared to AO‐1 and AO‐2. However, in the hybrid of catalysts due to the complex interaction between the catalysts, the MgCl 2 support and antioxidant showed different behaviors …”
Section: Resultsmentioning
confidence: 99%
“…The results suggested that the different antioxidants did not have a notable effect on the thermal properties of polymers when the single catalyst was used in the polymerization reactor, however, when the hybrid of two catalysts (Cat 3) was used in the polymerization reactor, the X c % changed from 43 to 60. This is probably due to difference in the structures of the catalysts used …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main strategies used for the improvement of polyolefin catalysts, which is still being investigated at the laboratory scale, is the use of a combination of different types of catalysts during polymerization. Catalyst alloys, hybrid catalysts and multi‐catalyst systems are commonly used in this respect . In these systems, each of the catalysts produces polymers with different properties, and therefore the final polymer is a blend of two or more kinds of polymers.…”
Section: Introductionmentioning
confidence: 99%